Participation of the Oviductal s100 Calcium Binding Protein G in the Genomic Effect of Estradiol That Accelerates Oviductal Embryo Transport in Mated Rats - Orihuela-Diaz, P; Croxatto -Avoni, H; Velasquez, L (BioMed Central Ltd., 2011)
Background: Mating changes the mechanism by which E2 regulates oviductal egg transport, from a non-genomic to a genomic mode. Previously, we found that E2 increased the expression of several genes in the oviduct of mated rats, but not in unmated rats. Among the transcripts that increased its level by E2 only in mated rats was the one coding for an s100 calcium binding protein G (s100 g) whose functional role in the oviduct is unknown.Methods: Herein, we investigated the participation of s100 g on the E2 genomic effect that accelerates oviductal transport in mated rats. Thus, we determined the effect of E2on the mRNA and protein level of s100 g in the oviduct of mated and unmated rats. Then, we explored the effect of E2on egg transport in unmated and mated rats under conditions in which s100 g protein was knockdown in the oviduct by a morpholino oligonucleotide against s100 g (s100 g-MO). In addition, the localization of s100 g in the oviduct of mated and unmated rats following treatment with E2was also examined.Results: Expression of s100 g mRNA progressively increased at 3-24 h after E2 treatment in the oviduct of mated rats while in unmated rats s100 g increased only at 12 and 24 hours. Oviductal s100 g protein increased 6 h following E2and continued elevated at 12 and 24 h in mated rats, whereas in unmated rats s100 g protein increased at the same time points as its transcript. Administration of a morpholino oligonucleotide against s100 g transcript blocked the effect of E2on egg transport in mated, but not in unmated rats. Finally, immunoreactivity of s100 g was observed only in epithelial cells of the oviducts of mated and unmated rats and it was unchanged after E2 treatment.Conclusions: Mating affects the kinetic of E2-induced expression of s100 g although it not changed the cellular localization of s100 g in the oviduct after E2. On the other hand, s100 g is a functional component of E2 genomic effect that accelerates egg transport. These findings show a physiological involvement of s100 g in the rat oviduct. © 2011 Ríos et al; licensee BioMed Central Ltd.